2017
DOI: 10.1007/s11356-017-0105-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants produced by Bacillus subtilis A1 and Pseudomonas stutzeri NA3 reduce longevity and fecundity of Anopheles stephensi and show high toxicity against young instars

Abstract: Anopheles stephensi acts as vector of Plasmodium parasites, which are responsible for malaria in tropical and subtropical areas worldwide. Currently, malaria management is a big challenge due to the presence of insecticide-resistant strains as well as to the development of Plasmodium species highly resistant to major antimalarial drugs. Therefore, the present study focused on biosurfactant produced by two bacteria Bacillus subtilis A1 and Pseudomonas stutzeri NA3, evaluating them for insecticidal applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…We found that biomass synthesis and rhamnolipids production increased linearly with the rate of metabolite uptake. Our simulation-based predictive results are in keeping with our labbased fermentation work previously carried out with Pseudomonas strains (Rahman et al, 2002;Rahman et al, 2009;Rahman et al, 2010;Joy et al, 2017;Parthipan et al, 2018). In addition, we also identified that myristic acid (C-14) provided optimal growth rate and rhamnolipids production compared to the other carbon sources in this study.…”
Section: Resultssupporting
confidence: 85%
“…We found that biomass synthesis and rhamnolipids production increased linearly with the rate of metabolite uptake. Our simulation-based predictive results are in keeping with our labbased fermentation work previously carried out with Pseudomonas strains (Rahman et al, 2002;Rahman et al, 2009;Rahman et al, 2010;Joy et al, 2017;Parthipan et al, 2018). In addition, we also identified that myristic acid (C-14) provided optimal growth rate and rhamnolipids production compared to the other carbon sources in this study.…”
Section: Resultssupporting
confidence: 85%
“…We found that biomass synthesis and rhamnolipids production increased linearly with the rate of metabolite uptake. Our simulation-based predictive results are in keeping with our lab-based fermentation work previously carried out with Pseudomonas strains (Rahman et al, 2002, 2009, 2010; Joy, Rahman & Sharma, 2017; Parthipan et al, 2018). In addition, we also identified that myristic acid (C-14) provided optimal growth rate and rhamnolipids production compared to the other carbon sources in this study.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, little is known about the role of the Pseudomonadacea family, highly abundant in BAG mosquitoes, in the development of the malaria parasite. However, specific products extracted from different species of Pseudomonas have shown to reduce the longevity and fecundity of A. stephensi mosquitoes [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%